Kajian Estetika Wayang Kulit pada Tokoh Dewa Ruci Koleksi Museum Wayang Jakarta - Alya Puspawati; Almira Belinda Z; Nuning Yanti Damayanti (LP2M ISBI Bandung, 2026)
Wayang is a visual representation of living beings used in performing arts to convey narratives, including the tale of Dewa Ruci. This study aims to comprehend the character of Dewa Ruci through the aesthetic meaning of its wayang kulit form, the visual influence of the manuscript, and its contribution to the visual conservation of artifacts related to wayang aesthetics. This research employs a qualitative methodology with an interdisciplinary approach. The theoretical framework consists of wayang aesthetic theory, encompassing wanda (character typology based on facial and bodily patterns) and puppet form classification, alongside RWD's visual language theory to support visual analysis. The analytical process applies Feldman's art criticism method to guide the examination of the sample. The Museum Wayang Jakarta houses a Yogyakarta-style Dewa Ruci wayang kulit characterized by a fuller bodily physique. The essential formal elements of the puppet reside in its wanda, the distinctive visible patterns of facial and bodily design. The wanda embodies a refined and religious character through a bowed head position and the use of black as a symbol of emotional restraint. The visual design of the Dewa Ruci puppet in this analysis is structured to communicate comprehensive information within a single view, reflecting a gentle character.